Real-world effectiveness of fremanezumab in patients with migraine switching from another mAb targeting the CGRP pathway: a subgroup analysis of the Finesse Study - Straube, Andreas; Broessner, Gregor; Gaul, Charly; Hamann, Xenia; Hipp, Joachim; Kraya, Torsten; Neeb, Lars (Journal of headache and pain, 2023)
Background Monoclonal antibodies targeting the CGRP pathway are effective and safe for prophylactic treatment of episodic (EM) and chronic migraine (CM). In case of treatment failure of a CGRP pathway targeting mAb, physician has to decide whether using another anti-CGRP pathway mAb is useful. This interim analysis of Finesse Study evaluates effectiveness of the anti-CGRP mAb fremanezumab in patients with a history of other prior anti-CGRP pathway mAb treatments (switch patients). Methods Finesse , a non-interventional, prospective, multicentre, two-country (Germany-Austria) study observing migraine patients receiving fremanezumab in clinical routine. This subgroup analysis presents data on documented effectiveness over 3 months after the first dose of fremanezumab in switch patients. Effectiveness was evaluated based on reduction in average number of migraine days per month (MMDs), MIDAS and HIT-6 scores changes as well as in number of monthly days with acute migraine medication use. Results One hundred fifty-three out of 867 patients with a history of anti-CGRP pathway mAb treatment prior to initiation of fremanezumab were analysed. Switch to fremanezumab led to ≥ 50% MMD reduction in 42.8% of migraine patients, with higher response rate in EM (48.0%) than in CM patients (36.5%). A ≥ 30% MMD reduction was achieved by 58.7% in CM patients. After three months, monthly number of migraine days decreased by 6.4 ± 5.87 (baseline: 13.6 ± 6.5; p < 0.0001) in all patients, 5.2 ± 4.04 in EM and 7.7 ± 7.45 in CM patients. MIDAS scores decreased from 73.3 ± 56.8 (baseline) to 50.3 ± 52.9 (after 3 months; p = 0.0014), HIT-6 scores decreased from 65.9 ± 5.0 to 60.9 ± 7.2 ( p < 0.0001). Concomitant use of acute migraine medication had decreased from 9.7 ± 4.98 (baseline) to 4.9 ± 3.66 (3 months) ( p < 0.0001). Conclusions Our results show that about 42.8% of anti-CGRP pathway mAb-non-responder benefit from switching to fremanezumab. These results suggest that switching to fremanezumab may be a promising option for patients experiencing poor tolerability or inadequate efficacy with prior other anti-CGRP pathway mAb use. Trial registration Finesse Study is registered on the European Network of Centres for Pharmacoepidemiology and Pharmacovigilance (EUPAS44606). Graphical Abstract